Cytotoxicity and mycotoxin production of shellfish‐derived Penicillium spp., a risk for shellfish consumers. (6th September 2013) - Geiger, M.; Guitton, Y.; Vansteelandt, M.; Kerzaon, I.; Blanchet, E.; Robiou du Pont, T.; Frisvad, J.C.; Hess, P.; Pouchus, Y.F.; Grovel, O.
Abstract In order to assess the putative toxigenic risk associated with the presence of fungal strains in shellfish‐farming areas, Penicillium strains were isolated from bivalve molluscs and from the surrounding environment, and the influence of the sample origin on the cytotoxicity of the extracts was evaluated. Extracts obtained from shellfish‐derived Penicillia exhibited higher cytotoxicity than the others. Ten of these strains were grown on various media including a medium based on mussel extract (Mytilus edulis), mussel flesh‐based medium (MES), to study the influence of the mussel flesh on the production of cytotoxic compounds. The MES host‐derived medium was created substituting the yeast extract of YES medium by an aqueous extract of mussel tissues, with other constituent identical to YES medium. When shellfish‐derived strains of fungi were grown on MES medium, extracts were found to be more cytotoxic than on the YES medium for some of the strains. HPLC‐UV/DAD‐MS/MS dereplication of extracts from Penicillium marinum and P. restrictum strains grown on MES medium showed the enhancement of the production of some cytotoxic compounds. The mycotoxin patulin was detected in some P. antarcticum extracts, and its presence seemed to be related to their cytotoxicity. Thus, the enhancement of the toxicity of extracts obtained from shellfish‐derived Penicillium strains grown on a host‐derived medium, and the production of metabolites such as patulin suggests that a survey of mycotoxins in edible shellfish should be considered. Significance and Impact of the Study Penicillium strains isolated from bivalve molluscs produce extracts exhibiting a higher cytotoxicity than extracts from Penicillium strains isolated from the surrounding marine environment. The use of a mussel‐based medium for cultures of some shellfish‐derived strains enhances the cytotoxicity of extracts when compared with classical media. The production of cytotoxic compounds and of the mycotoxin patulin on such a host‐derived medium highlights a potential health risk for shellfish consumers.